Regression Testing Process for Small Organization for Quality Software - Joseph, Jasmin.; Anand, K.Vijay (IJRDO -Journal of Computer Science Engineering, 2016)
Software has been component ofcurrent society for more than 50 years.There are more than a few softwaredevelopment methodologies in use today.This paper addresses the study in the part ofregression testing. Every time a system isaltered regression tests have to be run tovalidate these changes.Its well prepared setup and supportof its effecting is desired across smallorganizations developing software. The goalof this paper is to explain quality assuranceand software testing domains. In this paperimplementation is focused on smallorganizations, which develops commercial,off-the-shelf software. In this work problemsare identified and information and bestpractices are provided to help such type oforganizations with regression testing, andthereby with overall quality of theirproducts.